Technical Efficiency Analysis of Non-Chemical Pesticide Rice Farming in Rejoasri Village, Seputih Raman District - Sutarni, Sutarni; Fitriani, Fitriani; Berliana, Dayang; Andarwangi, Tunjung (Politeknik Negeri Bengkalis, 2024)
Rejoasri Village, Seputih Raman District, is one of the villages that implements sustainable agricultural practices, namely non-chemical pesticide rice farming that produces rice free of chemical pesticide residue